Bis(guanidinium) cyananilate - Udachin, Konstantin A. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, 2CH(6)N(3) (+)·C(8)N(2)O(4) (2−), contains one half of a centrosymmetric 2,5-dicyano-3,6-dioxocyclohexa-1,4-diene-1,4-diolate (cyananilate) anion and one guanidinium cation, which are connected by N—H⋯O and N—H⋯N hydrogen bonds into a three-dimensional network.